Cash transfers increase trust in local government - Evans, David K.; Holtemeyer, Brian; Kosec, Katrina (Elsevier, 2019)
How does a locally-managed conditional cash transfer program impact trust in government? On the one hand, delivering monetary benefits and increasing interactions with government officials (elected and appointed) may increase trust. On the other hand, it can be difficult for citizens to know to whom to attribute a program and reward with greater trust. Further, imposing paternalistic conditions and possibly prompting citizens to experience feelings of social stigma or guilt, could reduce trust. We answer this question by exploiting the randomized introduction of a locally-managed transfer program in Tanzania in 2010. Our analysis reveals that cash transfers can significantly increase trust in leaders. This effect is driven by large increases in trust in elected leaders as opposed to appointed bureaucrats. Perceptions of government responsiveness to citizens’ concerns and honesty of leaders also rise, and these improvements are largest where there are more village meetings at baseline. One of the central roles of village meetings is to receive and share information with village residents, providing some evidence on the value of a high-information environment for generating trust in government. We also find that records from school and health committees are more readily available in treatment villages. Notably, while stated willingness of citizens to participate in community development projects rises, actual participation in projects and the likelihood of voting do not. Overall, the results suggest little reason to worry that local management of a conditional cash transfer program reduces trust in government or the quality of governance—especially in high-information settings.